2019
DOI: 10.1021/acs.joc.9b00802
|View full text |Cite
|
Sign up to set email alerts
|

Polysubstituted Hexa-cata-hexabenzocoronenes: Syntheses, Characterization, and Their Potential as Semiconducting Materials in Transistor Applications

Abstract: A series of tetra- and octa-substituted hexa-cata-hexabenzocoronenes (cata-HBCs) were synthesized from tetraryl olefins via iodine- and iron chloride-catalyzed oxidative cyclodehydrogenation reactions. The substitutions on the periphery of the parent HBC serve to modify the photophysical properties, highest occupied molecular orbital–lowest unoccupied molecular orbital gaps, and thermal stabilities of the respective derivatives. The crystal structures were determined to display multiple twists in the framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…For example, strong F…F intermolecular interactions were observed in the self‐assembly of fluorinated cata ‐HBCs [215] . Our group reported photophysical properties and HOMO/LUMO energies of tetrasubstituted and polysubstituted cata ‐HBCs [72] . In addition, crystal structures of tetrasubstituted derivatives revealed that HBCs packed in perfect or shifted co‐facial styles, depending on the substitutions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, strong F…F intermolecular interactions were observed in the self‐assembly of fluorinated cata ‐HBCs [215] . Our group reported photophysical properties and HOMO/LUMO energies of tetrasubstituted and polysubstituted cata ‐HBCs [72] . In addition, crystal structures of tetrasubstituted derivatives revealed that HBCs packed in perfect or shifted co‐facial styles, depending on the substitutions.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, the syntheses of fluorine‐substituted HBCs were also successful like the parent and alkoxy‐substituted HBCs, although their olefin precursors were slightly deactivated towards the oxidative cycylodehydrogenation reactions [71] . Our group reported [72] tetra‐substituted HBCs, whose production required consecutive usage of iodine‐mediated oxidative photocyclization and Scholl protocol. Using similar two‐step strategy, many others such as polysubstituted HBCs were also harnessed in good yields.…”
Section: Resultsmentioning
confidence: 95%
“…The introduction of heteroatom into the framework results in a molecular dipole (Table S1), which may also impact the packing motifs. In the case of DPT series, near cofacial packing and thus good π‐π overlap of the frameworks for nearest neighbors was obtained for DPT and Cl‐DPT, presumably due to geometric complementarity, and possibly the Cl…Cl interaction …”
Section: Resultsmentioning
confidence: 98%
“…The effect of a small substituent such as electron‐donating/withdrawing dipoles is accountable for the minor difference, which is noticed in LUMO values. [ 19 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 ] Recently, we reported high‐efficiency SCFETs using contorted pyreno[4,5 ‐a ]coronenes, tetrabenzo[ a,d,j,m ]coronenes, and dibenzo[ a,d ]coronenes as the channel materials. [ 17–19 ] These compounds display exactly co‐facial or shifted co‐facial packing. These molecules are nevertheless more symmetrical in shape, which allows more opportunity in ordered crystal packing.…”
Section: Introductionmentioning
confidence: 99%